FACTORS ASSOCIATED TO INFLUENZA VACCINATION IN THE ELDERLY: AN INTEGRATIVE REVIEW: FATORES ASSOCIADOS À VACINAÇÃO CONTRA A INFLUENZA EM IDOSOS: UMA REVISÃO INTEGRATIVA - Moreira, Maria de Fátima da Silva; Paulo, Maria Eduarda de Sousa; Alves, Salmana Rianne Pereira; Silva, Glaydes Nely Sousa da (Revista de Ciências da Saúde Nova Esperança, 2021)
It is known that several reasons for the non-adherence of the elderly population to influenza vaccination are discussed in the literature. The understanding about such factors supports the development of strategies to encourage the search for vaccination. Thus, the present study aims at analyzing the main factors associated with the non-adherence to influenza vaccination among the elderly. This is an integrative review, conducted in the LILACS, SCIELO and PUBMED databases, having as descriptors: elderly; influenza and vaccination. As inclusion criteria: original research articles published in the last 12 years (2008 to 2020). Regarding the associated factors contributing to the non-adherence to vaccination, demographic characteristics, lack of time to go to the healthcare unit, refusal of vaccination for several reasons, lack of knowledge, illness after other previous vaccinations, the lack of interest in taking it, overall disbelief in the vaccine and not having information about the vaccine stand out. Thus, campaigns and projects that aim at educationally informing the elderly about vaccination, must encompass these aspects and implement specific strategies to satisfactorily reach the target audience's adhesion to influenza vaccination.